Reading the Music Revolution through the “The Song of the Nations” Film (1930) and “The Nightingale of Türkiye” (1931) Vocal Contests - Ceyhun Öğreten (Yakın Dönem Türkiye Araştırmaları)
Music is a cultural phenomenon with an important place in daily life practices. The Westernization movement that started with the Tanzimat during the Ottoman era was also reflected in the field of music and then placed on an academic basis during Türkiye’s Republican period. In the first years of the Republic, various ideas emerged about the content of the reforms to be made in the field of music. Atatürk stated that Turkish music should be based on folk music and that other reform efforts would be incomplete if no reform was made to music. In this context, Western-based institutional steps were taken in the field of music. Vocal competitions were held in 1930 and 1931 in order to internalize the targetedmusical revolution for the public. This study examines and evaluates the sound competitions held in 1930 and 1931 through the press of the time and the literature on this field within the framework of the music revolution.